Teachers’ Preparedness for Use of Computer Technology Tools in Teaching and Learning English Vocabulary in Grade Three in Primary Schools in Nyamira County, Kenya - Bernard , Nyasimi; Bernard , Mudogo; Teresa , Okoth (African Journal of Education,Science and Technology (AJEST), 2024)
Teachers' preparedness significantly influences the successful integration of computer technology into English language teaching and learning activities. The purpose of this study was to assess teachers’ preparedness for use of computer technology tools in teaching and learning English vocabulary in grade three in primary schools in Nyamira County, Kenya. The study used a mixed-methods research design, stratified simple random and purposive selection approaches to select a sample of 23 Curriculum Support Officers (CSOs) and 62 teachers who delivered English language activities to third-graders. Teachers completed a questionnaire to acquire quantitative data while CSOs participated in semi-structured interviews to collect qualitative data. Themes were used to categorize qualitative data, and narrative analysis was employed. Descriptive statistics such as percentages and frequencies were used to analyse quantitative data. The findings showed that primary school teachers were not adequately prepared to use computer technology tools in English vocabulary lessons. The findings indicated that insufficient training and limited competence in computer technology use contributed to teachers’ inadequate preparation for utilisation of computer technology tools in English vocabulary instruction. Therefore, to maximize the use of computer technology tools in English language teaching and learning activities, teachers should have access to opportunities for ongoing professional development to keep their knowledge and skills up to date.